IMPACT OF INCREASED NOISE LEVELS AT PUBLIC EVENTS IN KHOREZM REGION ON POPULATION HEALTH (Journal of Universal Science Research, 2025)
In recent years, the growing frequency of mass public events using powerful sound systems, particularly at weddings and celebrations in the Khorezm region, has raised public health concerns. Urbanization and the widespread use of amplified music contribute to increased environmental noise levels. According to the World Health Organization, prolonged exposure to noise levels exceeding 60 dB adversely affects the central nervous system, cardiovascular function, and immune regulation. These effects may contribute to the development of stress-related disorders and a decline in overall quality of life. Therefore, understanding the health implications of noise pollution in public gatherings is of great relevance.